Validation of selection signatures for coat color in the Podolica Italiana gray cattle breed - Bruno, Silvia; Rovelli, Giacomo; Landi, Vincenzo; Sbarra, Fiorella; Quaglia, Andrea; Pilla, Fabio; Lasagna, Emiliano; Ciani, Elena (Frontiers in Genetics, 2024)
Taurine and indicine gray cattle represent relevant livestock resources in many countries of the world. A gray coat color and pigmented skin, which are common in most of the gray cattle breeds, have been demonstrated to confer better adaptation to solar radiation and thermal stresses. In a previous study adopting the FST-outlier approach with BayeScan v2.0, we identified differentially selected genomic regions in a set of gray cattle breeds, including the Podolica Italiana, and contrasted these findings with four non-gray cattle breeds. More supported signals were detected on bovine chromosomes (BTAs) 2, 4, 14, and 26 that encompassed more than fifty genes known to be directly or indirectly related to one or more steps in pigment biology. In the present study, we aimed to validate the previously observed signals using the same methodological approach on three new Podolica Italiana sample sets (N = 30 animals each). These animals were selected from the ANABIC genetic station during performance tests as being representative of the Podolica Italiana population at three different timeframes separated by approximately 10 years each. We typed these samples to the loci of 23,027 quality-controlled single-nucleotide polymorphisms. We also analyzed the dataset using the haplotype-based approach available in hapFLK v1.4 software. Both the FST-outlier and hapFLK approaches validated the abovementioned signals on BTAs 2, 4, 14, and 26. Moreover, both methods detected additional supported regions on BTAs 7 and 18 that included a total of 42 genes, of which most were already known from literature to be implicated in pigmentation traits.